Peran Osis dalam Membentuk Lingkungan Berbahasa Arab - Nopandri, Ramdani; Setiyawan, Agung; Rahmadani, Mely; Baso, Rihlah Ilmiah; Munir, Zainuddin Mansur (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to examine the role of the Intra-School Student Organization (OSIS) in shaping the Arabic language environment (biah lugawiyah) at SMK Ulil Albab NW Gegek, East Lombok, West Nusa Tenggara. The problems raised are students' low practical Arabic skills due to theoretical learning and the lack of a language environment outside the classroom. This study uses a qualitative descriptive method with an educational anthropology approach, with data obtained through participatory observation and in-depth interviews with student council administrators, teachers, and students, as well as documentation of student council work programs, and is analyzed using the Miles and Huberman model. The results show that OSIS plays a role as the main driver of language activities, a motivator, and a role model for students through daily Muhādaṡah programs, Ilqā’ mufradāt, language boards, and language competitions, which are proven to improve speaking skills, foster motivation, and build Arabic language habits. These scientific findings are consistent with Krashen’s language acquisition theory, behaviorism about positive reinforcement, and the concept of contextual learning (CTL), so it can be concluded that OSIS is a key actor in creating a conducive, dynamic, and sustainable biah lugawiyah for the development of Arabic language skills at the pesantren-based secondary school level.